The invisible parade - Bardugo, Leigh (Little, Brown and Company, 2025)
There's a party tonight, but Cala doesn't want to go. While her family prepares for the celebration, Cala grieves her grandfather and tries to pretend she's not afraid. But when she is separated from her family at the cemetery, Cala encounters four mysterious riders who will show her she is actually quite brave after all. Adventure awaits readers of all ages on Día de Muertos​ in this stunningly original and lushly illustrated tour de force about family, love, and overcoming grief.